THE EFFECT OF ECONOMIC GROWTH, PROVINCIAL MINIMUM WAGE, AND INVESTMENT ON EMPLOYMENT IN DKI JAKARTA PROVINCE IN 2018-2022 - Safitri, Sahdia; Mukhtar, Saparuddin; Sebayang, Karuniana Dianta Arfiando (Faculty of Economics and Business, Universitas Negeri Jakarta, 2023)
The employment problem in Indonesia is not just limited opportunities or employment opportunities and low productivity. The increase in unemployment rates is caused by limited demand for work, which is then associated with other external factors including the decline in the balance of payments, increasing foreign debt and other policies which result in a decline in economic growth, decline in wages, investment and decline in employment. The purpose of this study is to determine the effect of Economic Growth, Provincial Minimum Wage, Investment, and Covid-19 Dummy on Employment in DKI Jakarta Province in 2018-2022. This study used multiple linear regression method with Generalized Least Square (GLS) model. This study uses secondary data while Covid-19 is included in the dummy variable category. The results of this study show that economic growth has a positive and significant influence on employment. Meanwhile, the provincial minimum wage, investment, and Covid-19 dummy have a negative and insignificant effect on labor absorption in DKI Jakarta Province in 2018-2022.